1993
DOI: 10.1007/bf02053502
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins or lactulose for the prevention of the recurrence of colorectal adenomas

Abstract: Colonic adenomas represent the natural precursor lesions of most colorectal cancers. The treatment of choice is endoscopic polypectomy. However, after endoscopic removal, polyps recur in a large fraction of cases. Thus, we evaluated the effect of antioxidant vitamins or lactulose on the recurrence rate of adenomatous polyps. After polypectomy, 255 individuals were randomized into three groups. Group 1 was given vitamin A (30,000 IU/day), vitamin C (1 g/day), and vitamin E (70 mg/day); Group 2 was given lactulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Some studies have been performed in patients with colorectal adenomas, an intermediary end point, examining the recurrence rate after polypectomy [37][38][39][40][41]. However, as malignant potential increases proportionately with polyp size [42,43], growth rate may be of greater importance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been performed in patients with colorectal adenomas, an intermediary end point, examining the recurrence rate after polypectomy [37][38][39][40][41]. However, as malignant potential increases proportionately with polyp size [42,43], growth rate may be of greater importance.…”
Section: Introductionmentioning
confidence: 99%
“…In trials of people with a history of asbestos exposure, a combined dose of beta-carotene and retinol led to a slightly elevated incidence of lung cancer (Omenn et al, 1996) whereas another study found no differences in sputum atypia over a shorter period (McLarty et al, 1995). There does not seem to be another trial that has used beta-carotene combined with vitamin C. Trials using adenomatous colonic polyps as the outcome have tested various other combinations of beta-carotene, vitamin C, vitamin E and retinol (McKeown-Eyssen et al, 1988;DeCosse et al, 1989;Roncucci et al, 1993;Greenberg et al, 1994;MacLennan et al, 1995). Only Roncucci et al (1993), who used 1000 mg vitamin C plus 70 mg alphatocopherol plus 9 mg retinol (not beta-carotene), have found a favourable effect on the recurrence rate of adenomatous polyp.…”
Section: Discussionmentioning
confidence: 99%
“…There does not seem to be another trial that has used beta-carotene combined with vitamin C. Trials using adenomatous colonic polyps as the outcome have tested various other combinations of beta-carotene, vitamin C, vitamin E and retinol (McKeown-Eyssen et al, 1988;DeCosse et al, 1989;Roncucci et al, 1993;Greenberg et al, 1994;MacLennan et al, 1995). Only Roncucci et al (1993), who used 1000 mg vitamin C plus 70 mg alphatocopherol plus 9 mg retinol (not beta-carotene), have found a favourable effect on the recurrence rate of adenomatous polyp.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study of patients with sporadic adenomas found no effect of supplemental vitamin C and E on the rate of recurrence of adenomas over a two-year period among 143 patients randomly assigned to vitamins or placebo (19). However, an Italian trial revealed a statistically significant reduction in the incidence of adenomas after supplementation with vitamins A, C and E (20). In the Polyp Prevention Study involving six clinical centers in the US, treatment for four years with either betacarotene or vitamins C and E did not affect the rate of occurrence of new adenomas in patients who had had an adenoma removed before entering the study (21).…”
Section: Pharmacologic Interventionmentioning
confidence: 99%